Analisis Perbedaan Tingkat Motivasi Belajar Mahasiswa Beasiswa KIP-K Merdeka Angkatan 2023 di Universitas Sanata Dharma Ditinjau dari Jenis Kelamin - Septiani Eka Putri; Robertus Budi Sarwono (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This research aims to (1) Describe the level of learning motivation of female and male students receiving KIP-K scholarships class of 2023 at Sanata Dharma University. (2) Knowing the differences in the level of learning motivation of students receiving the KIP-K scholarship class of 2023 at Sanata Dharma University in terms of gender. (3) Identifying items with low scores as a basis for proposing appropriate guidance service topics to help increase learning motivation among scholarship recipient students. This type of research uses quantitative methods with comparative descriptive analysis units. The subjects in this research were students who received the KIP-K scholarship class of 2023 at Sanata Dharma University, totaling 70 students from a total population of 114 students. The questionnaire was prepared based on aspects of learning motivation according to Santrock (2004). The research results show that there is no significant difference in the level of learning motivation between female and male students as seen from the p value of 0.286 > 0.05. Women have a very high level of learning motivation and men have a high level of learning motivation. Keywords: , ,